Investigating the Nature of Plasma Oscillations in Cold Plasma - Joshi, Prem Raj; Chaudhary, Keshab (Far Western Review, 2023)
Plasma oscillations are one of the important phenomena in plasma. The research in the field of plasma oscillation has a long history for more than six decades. The cold plasma is one in which electron temperature is very large but the neutral atoms are at room temperature. This study aims to obtain electron number density, electric field and velocity profile in cold plasma. Analytical method has been used to conduct this study. Fluid equations were solved to get the solution for number density, electric field and velocity of electron. To get the solution, first fluid equations are transferred to Lagrangian co-ordinates, where equations become linear and expression for respective parameter was obtained. A sinusoidal perturbation was taken as an initial condition and solution for number density; electric field and velocity were obtained. Value of perturbation was varied and corresponding waveforms were achieved and analyzed. As the perturbation increases the wave amplitude also increased. It is found that as the perturbation value is there is wave breaking in number density profile. Unlike in the number density, no such wave breaking is obtained for electric field and velocity profile. However the amplitude of waveform of electric field and velocity profile found to increases with increase in perturbation level.